First detection of equine hepacivirus RNA in Stomoxys calcitrans (Diptera, Muscidae) in eastern Austria - Vicky Frisch; Anna Sophie Ramsauer; Irina Preining; Maria S. Unterköfler; Hans-Peter Fuehrer; Martin Hofer; Manolis Lyrakis; Emilie Bouhsira; Emmanuel Liénard; Jessika-M. V. Cavalleri (BMC Veterinary Research)
Abstract Background Equine hepacivirus (EqHV) from the Flaviviridae family, has been detected in horses worldwide with a global RNA prevalence of up to 7.9%. While vertical transmission and iatrogenic transmission with infected blood products have been demonstrated for this virus, field infection rates suggest an additional horizontal transmission route. The aim of this study was to investigate the potential role of Stomoxys calcitrans (Diptera, Muscidae) – a hematophagous fly that is found in stables with ruminants and horses as preferred hosts– in the transmission of EqHV RNA. Materials and methods From 2021 to 2022, S. calcitrans were collected from three horse barns in eastern Austria. The abdomen of each fly was separated from the head and thorax. The heads and thoraxes, including wings and legs were subsequently pooled, with a maximum of five flies per pool, and assayed for the presence of EqHV using a one-step RT-qPCR. For all positive pools, the corresponding abdomens were analysed individually using the same EqHV one-step RT-qPCR. Results A total of 783 S. calcitrans were collected at the three locations. EqHV RNA was detected in 7/136 pools of heads and thoraxes, including wings and legs, in 2021 and in 7/53 pools in 2022. Most positive pools were detected in autumn. The Ct values of the RT-qPCR were close to the presumed limit of detection. Additionally, EqHV RNA could be detected in 34 of 40 abdomens from 2021 to 20 of 40 abdomens from 2022, validating the results of the positively tested head/thorax pools. The minimum infection rate (MIR) was 1.2% in 2021 and 3.9% in 2022. The maximum likelihood estimation (MLE) was 1.2% in 2021 and 3.9% in 2022. Conclusion Although the amounts of viral RNA were close to the limit of detection, the positive abdomens confirmed an up-take of virus-contaminated blood by the flies, and viral RNA residues were detected in the head and thorax. These results indicate that S. calcitrans may harbor EqHV in their head and thorax regions.